Analyzing Grammatical Errors Committed by Students in Writing in the Academic Year 2020/2021 - Deviyanti, Ni Made; Dambayana Suputra, Putu Eka; Adi Krisna Juniarta, Putu (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p04, 2021)
This study aimed to analyze the types of errors in writing recount texts and identify the source of errors in students. The subjects of this study were tenth-grade students of Languages major ??at SMA Negeri 1 Kuta Selatan with a total of 31 students. This research was qualitative descriptive research. Data were collected from students' writing assignments, questionnaires, and interviews. This study used the theory of Dulay et al. (1982) to find out the types of errors supported with the theory from Sawalmeh (2013) regarding spelling errors which was supported by the theory from Besten & Granger (2011). The theory from Brown (2007) was used to find out the source of students' errors. The results of this study indicate that the types of errors found in student texts are omission, misformation, addition, misordering, and spelling. Sources of student errors are interlingual transfer, intralingual transfer, the context of learning, and communication strategy .